Nanosilver Doped Poly-Phenylene-Sulfide Polymer Conductor - Mohammad Hatta, Mohammad Asyraf (Curtin University, 2019)
This study investigated a novel method by nanosilver particles doped into poly (p-phenylene sulfide) (PPS) to enhance its charge transfer. Pure PPS was doped with nanosilver in various parameters. Investigation on threshold melting temperature identified the effective melting temperature as 420°C. Variation of nanosilver concentrations revealed the change in conductivity approaching germanium metalloid at 1.5x10-01 S/cm. FTIR analysis had further conforms the delocalization of the Π-bonds electron in the polymer chain.